2008
DOI: 10.1186/gb-2008-9-4-r65
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition accelerates the early events of stem cell differentiation: transcriptomic and epigenetic analysis

Abstract: Histone deacetylase inhibition in stem cell differentiation

A gene profiling study of mouse embryonic stem cells treated with the histone deacetylase inhibitor trichostatin A shows that inhibition of histone deacetylases accelerates the early events of differentiation, by regulating the expression of pluripotency-and differentiation-associated in an opposite manner.

Abstract Background: Epigenetic mechanisms regulate gene expression patterns affecting cell function and differentiation. In this report, w…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 46 publications
7
97
0
1
Order By: Relevance
“…Brief histone hyperacetylation induced by TSA treatment induced nestin expression in P19 EC cells and enhanced proneural and Sox2 neural gene expression when performed at the neural progenitor stage (24). In other contexts, hyperacetylation of chromatin enhances cellular plasticity and facilitates somatic cell reprogramming (32,33). Together, these findings suggest that open and acetylated chromatin is conducive to promoting early and multipotential cell states including neural precursors.…”
Section: Discussionmentioning
confidence: 52%
“…Brief histone hyperacetylation induced by TSA treatment induced nestin expression in P19 EC cells and enhanced proneural and Sox2 neural gene expression when performed at the neural progenitor stage (24). In other contexts, hyperacetylation of chromatin enhances cellular plasticity and facilitates somatic cell reprogramming (32,33). Together, these findings suggest that open and acetylated chromatin is conducive to promoting early and multipotential cell states including neural precursors.…”
Section: Discussionmentioning
confidence: 52%
“…9 Several studies have shown that patterns of histone modification have been associated with many essential biological processes, such as stem cell maintenance and differentiation. 10,16,21 Previous studies have revealed that mesenchymal stem cells exist in ligamentum flavum and play a crucial role in the development of OLF. 3,18 Whether histone modifications are involved in this ossification process has not been studied.…”
mentioning
confidence: 99%
“…9,10,16,21 After translation of histone proteins, their N-terminal tails are susceptible to a range of covalent modifications, such as acetylation, methylation, phosphorylation, and ubiquitination.…”
mentioning
confidence: 99%
“…Knockdown of the expression of histone deacetylase 1 (Hdac1) in rat mesenchymal stem cells from bone marrow increased the levels of expression of cardiomyocyterelated genes [49]. It has been proposed that the inhibition of histone deacetylase activity downregulates the expression of genes characteristic for the undifferentiated state but upregulates differentiation-associated genes, thus accelerating the onset of differentiation [50]. One of the characteristics of the undifferentiated state is chromatin hyperplasticity, warranting the access of the nuclear transactions machinery to DNA.…”
Section: Cardiomyocytes Produced By Differentiation Ofmentioning
confidence: 99%